Cognitive wealth and fintech startup formation: an entrepreneurial absorptive capacity analysis in well-regulated environments - Madrazo-Lemarroy, Pilar; Márquez-Illescas, Gilberto; Moya-Ponce, Claudine (Springer, 2024)
Financial technology (fintech) startups have emerged as a compelling and digital alternative within the financial industry. However, the expansion is crucial because without proper regulation, the emergence of fintech in any country can potentially jeopardize its financial stability. In this empirical work, we analyze the emergence of fintech startups in the financial industry of a set of countries, focusing on human capital elements and regulatory environments. The study proposes a positive effect of a country’s knowledge-based capabilities on the creation of fintech startups through the country’s entrepreneurial absorptive capacity by adopting the theoretical framework of the Absorptive Capacity Theory of Knowledge Spillover Entrepreneurship. Moreover, we argue that the regulatory framework also plays a significant role in moderating the impact of entrepreneurial absorptive capacity on the establishment of fintech startups in any given country. We test our theoretical predictions using ordinary least squares and negative binomial regressions on a sample of 56 countries during the period 2008–2017. Our study demonstrates that the regulatory framework, previously regarded as a direct factor influencing fintech startup creation, also plays a significant role in moderating the impact of entrepreneurial absorptive capacity on the establishment of fintech startups. Furthermore, we find that this role may be influenced by the level of corruption in the economy and the specific types of fintech firms. These findings highlight that the drivers of fintech company creation are interconnected and work in conjunction to provide entrepreneurs with appropriate incentives to initiate new fintech ventures. © 2024 Springer Nature
Keywords: Fintech startups; Cognitive wealth; Entrepreneurial absorptive capacity; Regulation; Corruption